2019
DOI: 10.3389/fimmu.2019.01177
|View full text |Cite
|
Sign up to set email alerts
|

Differential Pathogenic Th17 Profile in Mesenteric Lymph Nodes of Crohn's Disease and Ulcerative Colitis Patients

Abstract: The drug targets IL23 and IL12 regulate pathogenicity and plasticity of intestinal Th17 cells in Crohn's disease (CD) and ulcerative colitis (UC), the two most common inflammatory bowel diseases (IBD). However, studies examining Th17 dysregulation in mesenteric lymph nodes (mLNs) of these patients are rare. We showed that in mLNs, CD could be distinguished from UC by increased frequencies of CCR6 + CXCR3 − RORγ + Tbet − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Altogether, our data demonstrate that in HD and UC patients the Lactobacillus and Bifidobacterium strains studied in this work interfere with the uptake and persistence of LF82 within dendritic cells, and are all able to interfere with the IL-23/Th17 axis, to a similar extent as the anti-inflammatory drug 6MP, while also stimulating production of the anti-inflammatory cytokine IL-10. In contrast, in CD-derived dendritic cells, probiotic strains, except for B. breve Bbr8 strain, are much less effective in affecting LF82-induced inflammatory response and in hampering release of the polarizing IL-1β and IL-23 cytokines that regulate differentiation of pathogenic Th17 cells [75,76]. Moreover, the protective effect of probiotic strains on DCs, in addition to downregulating proinflammatory cytokines, should promote tolerance-inducing DCs through the upregulation of IL-10, which plays an important regulatory role on effector T-cells [77].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our data demonstrate that in HD and UC patients the Lactobacillus and Bifidobacterium strains studied in this work interfere with the uptake and persistence of LF82 within dendritic cells, and are all able to interfere with the IL-23/Th17 axis, to a similar extent as the anti-inflammatory drug 6MP, while also stimulating production of the anti-inflammatory cytokine IL-10. In contrast, in CD-derived dendritic cells, probiotic strains, except for B. breve Bbr8 strain, are much less effective in affecting LF82-induced inflammatory response and in hampering release of the polarizing IL-1β and IL-23 cytokines that regulate differentiation of pathogenic Th17 cells [75,76]. Moreover, the protective effect of probiotic strains on DCs, in addition to downregulating proinflammatory cytokines, should promote tolerance-inducing DCs through the upregulation of IL-10, which plays an important regulatory role on effector T-cells [77].…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology | www.frontiersin.org December 2019 | Volume 10 | Article 1486 pathogenesis of CD (Brand, 2009;Ramos et al, 2017). Th17 cells mainly participate in and promote the occurrence and development of autoimmunity, while secreting many proinflammatory cytokines, including IL-17, TNF-α, INF-γ, IL-1β, IL-6, IL-8, IL-21, IL-22, GM-CSF, as well as adhesion molecules ICAM-1, VCAM-1, which can induce and amplify inflammation (Bsat et al, 2019). In addition, Th1 cells can secrete IFNγ, TNF-α and IL-2, resulting in inflammation and intestinal mucosal damage (Bsat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells mainly participate in and promote the occurrence and development of autoimmunity, while secreting many proinflammatory cytokines, including IL-17, TNF-α, INF-γ, IL-1β, IL-6, IL-8, IL-21, IL-22, GM-CSF, as well as adhesion molecules ICAM-1, VCAM-1, which can induce and amplify inflammation (Bsat et al, 2019). In addition, Th1 cells can secrete IFNγ, TNF-α and IL-2, resulting in inflammation and intestinal mucosal damage (Bsat et al, 2019). Previous studies have shown that the ratio of Th17 and Th1 cells in peripheral blood and intestinal mucosa was increased significantly in active CD while Treg cells were obviously decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that diseases can lead to a changing microenvironment resulting in localized changes to the inflammatory cytokine milieu that reshapes the adaptive immune response (22)(23)(24)48). With such changes, adaptive effector or tissue memory CD4 + T cell may be impacted through transdifferentiation leading to greater pathologic phenotypes (26,(49)(50)(51)(52). We were interested in determining if the adaptive CD4 + T cell response to sustained dysbiosis elicited by the keystone pathogen Pg resulted in transdifferentiation in Th17 and Treg cells in the oral mucosa.…”
Section: Transdifferentiation Of Il-17a Cre Fate-tracked Cellsmentioning
confidence: 99%
“…To address this question, we used two different fate-tracking reporter mouse strains to examine plasticity in Th17 or Treg cells, in a murine model of periodontitis (23,37). Transdifferentiation of Th17 cells is well documented (21-23, 26, 53) and a late developmental switch to IFN-γ expression in Th17 cells has been implicated in the pathologies of a diverse group of inflammatory autoimmune diseases such as psoriatic arthritis, Crohn's disease, ulcerative colitis, type 1 diabetes, and multiple sclerosis (23,26,(49)(50)(51)(52)54). Similarly, there have been reports that Treg cells also can transdifferentiate into IFN-γ-producing Th1-like cells (29,30,(55)(56)(57).…”
Section: Transdifferentiation Of Il-17a Cre Fate-tracked Cellsmentioning
confidence: 99%